أثر وحدات تدريبية مقترحة بالتدريب البليومتري في تطوير القوة الانفجارية لأطراف السفلية ومهارات التصويب لدى لاعبي كرة السلة أقل من 17 سنة - قولقسيس محمد رضا/قاسمي علال (Institut d’Éducation Physique et Sportive / UNIVERSITY OF MOSTAGANEM, 2025)
" أثر وحدات تدريبية مقترحة بالتدريب البليومتري في تطوير القوة الانفجارية لأطراف السفلية ومهارات التصويب لدى لاعبي كرة السلة أقل من 17 سنة" التدريب الرياضي أصبح يعتمد على الأسس والمبادئ العلمية مما يتيح ظهور عديد من الاساليب وطرق التدريب الحديثة منها طريقة التدريب البيلومتري الذي انتشر صداها عند المدربين واهل الاختصاص الذي يحتوي على مختلف تمارين الوثب التي تستهدف القوة الانفجارية بشكل خاص حيث تهدف هذه الدراسة إلى التعرف على أثر الوحدات التدريبية المقترحة بالتدريب البليومتري لتنمية القوة الانفجارية ومهارات التصويب لدى لاعبي كرة السلة أقل من 17 سنة، والكشف عن الفروق الإحصائية بين المجموعة الضابطة والمجموعة التجريبية في الاختبار البعدي للقوة الانفجارية واخر للمهارة التصويب حيث اعتمد الطالبان على المنهج التجريبي بتصميم المجموعتين المتكافئتين ضابطة وتجريبية وتمثلت عينة الدراسة في فريق أفاق مستغانم للكرة السلة صنف أقل من 16 سنة والبالغ عددها 10 لاعبين كعينة أساسية و 10لاعبين كعينة ضابطة و 08 لاعبين عينة استطلاعية، حيث استخدم الباحثان الاختبارات البدنية ومهارية كأدوات الجمع البيانات، وأسفرت نتائج الدراسة على أن للوحدات التدريبية بالتدريب البليومتري أثر إيجابي في تطوير القوة الإنفجارية ومهارات التصويب لدى لاعبي كرة السلة أقل من 17 سنة، ويوصي الطالبان بضرورة استخدام التدريبات البليومترية لتطوير مختلف الصفات البدنية الضرورية لرياضة كرة السلة ولكل الفئات العمرية. // // // // // "The effect of proposed plyometric training modules on developing explosive strength of the lower extremities and shooting skills in basketball players under 17 years of age." Sports training has become based on scientific foundations and principles, enabling the emergence of many modern training methods and techniques, including plyometric training, which has become popular among coaches and specialists. This method includes various jumping exercises that specifically target explosive strength. This study aims to identify the effect of the proposed plyometric training units on developing explosive strength and shooting skills in basketball players under 16 years old, and to detect statistical differences between the control group and the experimental group in the post-test for explosive strength and another for shooting skills. The students relied on the experimental method by designing two equivalent groups: a control group and an experimental group. The study sample consisted of the "AfakMostaganem basketball team" under 16 years old, consisting of 10 players as the primary sample, 10 players as the control sample, and 5 players as the experimental group. Exploratory, where the researchers used physical and skill tests as data collection tools. The study results showed that plyometric training modules have a positive effect on developing explosive power and shooting skills in basketball players under 16 years of age. The two students recommend the use of plyometric training to develop the various physical attributes necessary for the sport of basketball and for all age groups.
LES-2025-8
Keywords: : التدريب البليومتري; القوة الانفجارية; التصويب